2021
DOI: 10.21203/rs.3.rs-131380/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Age-dependent pathogenic characteristics of SARS-CoV-2 infection in ferrets

Abstract: While the seroprevalence of SARS-CoV-2 in healthy people does not differ significantly among age groups, those aged 65 years or older exhibit strikingly higher COVID-19 mortality compared to younger individuals. To further understand differing COVID-19 manifestations in patients of different ages, three age groups of ferrets were infected with SARS-CoV-2. Although SARS-CoV-2 was isolated from all ferrets regardless of age, aged ferrets (≥ 3 years old) showed higher viral loads, longer nasal virus shedding, and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 49 publications
2
7
0
Order By: Relevance
“…Our findings showing higher susceptibility of aged ferrets to SARS-CoV-2 infection in the present study parallel clinical observations in humans, which point to increased susceptibility and higher levels of virus replication in the respiratory tract of older people compared to young children ( 8 , 10 ). Additionally, results presented here corroborate findings of a recent study by Kim and collaborators ( 31 ), who showed age-related differences in viral load in the respiratory tract and lung histopathology in ferrets inoculated with SARS-CoV-2. This study also showed that expression levels of genes related to the interferon (IFN) pathway, activated T cells, and macrophage responses were increased in older ferrets following SARS-CoV-2 infection ( 31 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings showing higher susceptibility of aged ferrets to SARS-CoV-2 infection in the present study parallel clinical observations in humans, which point to increased susceptibility and higher levels of virus replication in the respiratory tract of older people compared to young children ( 8 , 10 ). Additionally, results presented here corroborate findings of a recent study by Kim and collaborators ( 31 ), who showed age-related differences in viral load in the respiratory tract and lung histopathology in ferrets inoculated with SARS-CoV-2. This study also showed that expression levels of genes related to the interferon (IFN) pathway, activated T cells, and macrophage responses were increased in older ferrets following SARS-CoV-2 infection ( 31 ).…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, results presented here corroborate findings of a recent study by Kim and collaborators ( 31 ), who showed age-related differences in viral load in the respiratory tract and lung histopathology in ferrets inoculated with SARS-CoV-2. This study also showed that expression levels of genes related to the interferon (IFN) pathway, activated T cells, and macrophage responses were increased in older ferrets following SARS-CoV-2 infection ( 31 ). These changes are likely due to enhanced immune responses following higher viral replication in aged animals.…”
Section: Discussionsupporting
confidence: 92%
“…Three-year-old ferrets had fevers that lasted out past 10 dpi. In addition, older ferrets lost more weight upon infection and regained it more slowly than younger ferrets [ 80 ]. More severe lung pathology also was noted in the older ferrets at 5 dpi.…”
Section: Age and Comorbiditiesmentioning
confidence: 99%
“…Nonhuman primate (12)(13)(14), ferret (15)(16)(17) and mouse (18) models that have been developed to understand SARS-CoV-2 pathogenesis and test vaccine and therapeutics efficacies display a mild course of disease. The lack of overt symptoms in NHPs and ethical constraints due to the sheer numbers required to recapitulate low frequency human cases with severe clinical manifestations limits the ability to understand all aspects of the disease and vaccine effectiveness.…”
Section: Introductionmentioning
confidence: 99%